Unveiling the Landscape of Sustainable Logistics Service Quality: A Bibliometric Analysis - Shereen Abdelaziz; Munjiati Munawaroh (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
In today's environmentally conscious world, where environmental sustainability and consumer demand for responsible business practices are Sustainable Logistics Service Quality (SLSQ) has emerged as a critical focus in supply chain management, driven by increasing environmental concerns and consumer demand for responsible business practices. This study conducts a bibliometric analysis of 546 Scopus-indexed documents published between 1994 and 2024, systematically uncovering key research trends, thematic clusters, and gaps in SLSQ. Findings reveal a marked increase in SLSQ research since 2013, spurred by regulatory pressures, advancements in digital technologies, and growing consumer expectations for sustainable logistics. Dominant themes include the integration of cutting-edge technologies such as artiﬁcial intelligence (AI), big data analytics, blockchain, and sustainable transportation methods, which collectively enhance logistics service quality while reducing environmental impacts. Additionally, a notable trend is the alignment of logistics services with sustainability goals, reﬂecting both academic interest and industry imperatives to lower carbon footprints and improve resource eﬃciency, particularly in sectors like e-commerce. Despite these advancements, the study identiﬁes signiﬁcant gaps, particularly the lack of multidimensional metrics capable of comprehensively evaluating SLSQ across social, environmental, and economic dimensions. This highlights an urgent need for standardized and holistic frameworks to guide logistics providers in achieving operational eﬃciency and sustainability objectives. By bridging service quality and sustainability, this research addresses an underexplored area and provides a foundation for future scholarly work in SLSQ. Practical implications include guiding logistics providers and policymakers in formulating sustainable practices that align with regulatory requirements and enhance customer satisfaction. For academia, it oﬀers a pathway to develop robust SLSQ metrics and frameworks, advancing sustainable logistics strategies and fostering a more eﬃcient, eco-friendly, and customer-centric logistics ecosystem.